The effectiveness of rubber technology transfer through program Pemaju Masyarakat RISDA (PMR) in selected states of Malaysia - Ismail, Mazlan (2015)
Rubber commodity contributes almost RM57 billion in 2012. With a total planting area of 1.04 million hectares, the contribution of this commodity to the national economy is expected to continue to increase due to high demand from the new economy powers like China and India. RISDA, is fully responsible in the smallholder sector, which includes 95% of the crop area and production of rubber, play a very important role in ensuring that this industry continues to expand and maintain Malaysia as one of the world's leading producer of natural rubber. Thus, some of the initiatives committed by RISDA is to appoint a total of 513 Pemaju Masyarakat RISDA (PMR) among proactive, good leadership and committed smallholder to jointly RISDA officers in the field in carrying out the delivery of extension services and technology transfer, especially to 265,274 rubber smallholders. Therefore, by creating PMR throughout the area of operations, RISDA really hope they can assist RISDA officers in the field in delivering the latest technologies in practiced as well as providing and gives a good return to smallholders. The objective of the study is to identify the demographics and farm characteristic of respondent in the study area, to examine the perception level of respondent toward PMR and RISDA extension programme. It’s also to clarify the relationship between social demographics and farm profile with the opinion and changing on smallholder farm management, productivity and family living status. 180 smallholders in Temerloh and Jerantut district were selected as respondents and interviewed to fulfill the requirement of this study. The data collected were analyzed by using descriptive analysis and chi-square analysis. The result of this study shows, the demographic and farm profile have no relationship with changing on smallholder farm management, productivity and familiy living status. As conclusion, there is need some improvement such as, PMR must constantly update and proficient in all the technologies was introduced and easily to be delivered to smallholders. Communication and collaboration with RISDA officers in the field should be maintained in order to achieve the target.